DNA-BASED IDENTIFICATION OF PROCESSED MEAT ADULTERATION WITHIN KADUNA METROPOLIS (FUDMA JOURNAL OF SCIENCES, 2024)
Processed meat adulteration poses significant risks to consumer’s health and trust, with fraudulent practices like meat substitution, filler addition, and false labeling compromising product quality and authenticity. Insufficient regulatory oversight exacerbates these issues, necessitating stricter regulations, improved inspection procedures, and increased consumer awareness to ensure the safety and transparency of processed meat products. This study employed a DNA-based approach to detect adulteration in processed meats using primers specific to cattle cytochrome C oxidase, pig cytochrome C oxidase, and chicken 12S rRNA. Forty-four processed meat samples, including beef meat pie (8), chicken meat pie (8), beef minced meat (9), chicken minced meat (9), pork steak (5), and pork balangu (5), were randomly collected from stores in four Kaduna Metropolis markets: Central Market, Sabon Tasha, Barnawa, and Kawo. Results showed that 25.0% of beef meat pies and 77.8% of beef minced meat were adulterated, with an overall adulteration level of 52.9% for processed beef. For processed chicken, 37.5% of chicken meat pies and 44.4% of chicken minced meat were adulterated, yielding an overall 41.2% adulteration rate. All ten processed pork samples were authentic. Central Market samples had a 40% adulteration rate, with 50% involving beef and 50% chicken. Sabon Tasha showed 9.1% beef adulteration. Barnawa had 30.8% adulteration, with 25.0% beef and 75.0% chicken. Kawo recorded a 70.0% adulteration rate, with 42.9% beef and 57.1% chicken. These findings demonstrate the effectiveness of DNA-based methods in detecting processed meat adulteration.
Keywords: Multiplex PCR; DNA; Adulteration; Primer; Processed meat